2000
DOI: 10.1152/ajpregu.2000.278.1.r111
|View full text |Cite
|
Sign up to set email alerts
|

Aging does not contribute to the decline in insulin action on storage of muscle glycogen in rats

Abstract: Increase in fat mass (FM) and changes in body composition may account for the age-associated impairment in insulin action on muscle glycogen storage. We wish to examine whether preventing the increase in FM abolishes this defect seen with aging. We studied the novel aging model of F1 hybrids of BN/F344 NIA rats fed ad libitum (AL) at 2 (weighing 259+/-17 g), 8 (459+/-17 g), and 20 (492+/-10 g) mo old. To prevent the age-dependent growth in FM, rats were caloric restricted (CR) at 2 mo by decreasing their daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
7
19
1
Order By: Relevance
“…Significant reductions of AT observed in this study in the aging group are consistent with previous results (15) obtained in similarly aged Sprague-Dawley rats. However, significant reductions of lean body mass, also seen in the aging group in this study, were not observed in three previous studies (6,7,12) of age-related changes of body composition in similarly aged rats. This may be due to the fact that different strains of rat were used in each of the studies considered.…”
Section: Treatment Effects On Body Compositioncontrasting
confidence: 92%
“…Significant reductions of AT observed in this study in the aging group are consistent with previous results (15) obtained in similarly aged Sprague-Dawley rats. However, significant reductions of lean body mass, also seen in the aging group in this study, were not observed in three previous studies (6,7,12) of age-related changes of body composition in similarly aged rats. This may be due to the fact that different strains of rat were used in each of the studies considered.…”
Section: Treatment Effects On Body Compositioncontrasting
confidence: 92%
“…All rats were fed ad libitum using regular rat diet that consisted of 64% carbohydrate, 30% protein, and 6% fat, with a physiological fuel value of 3.3 kcal/g food. At 1 week before the in vivo study, rats were anesthetized by inhalation of methoxyflurane, and indwelling catheters were inserted in the right internal jugular vein and left carotid artery (22)(23)(24)(25)(26). This method of anesthesia allows fast recovery and normal food consumption after 1 day.…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was assessed as described earlier (22)(23)(24)(25)(26). Briefly, rats received an intra-arterial bolus injection of 20 Ci of tritiated-labeled water ( 3 H 2 O; Du Pont-NEN, Boston, MA), and plasma samples were obtained at 30-min intervals for 3 h. Steady-state conditions for plasma 3 H 2 O-specific activity were achieved within 45 min in all studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucose clamp procedures were performed in awake, precatheterized, unrestrained, unanesthetized rats as described (7,9,10). Briefly, rats were fasted for 6 h, and a 2-h hyperinsulinemic euglycemic clamp procedure was conducted.…”
Section: Rat Models Usedmentioning
confidence: 99%